Lung MRI in Children: The Road Less Travelled - Sodhi, Kushaljit Singh (Indian Journal of Radiology and Imaging, 2021)
Magnetic resonance imaging (MRI) of the lungs is one of the most underutilized imaging modality when it comes to imaging of thoracic diseases in children. This is largely due to less-than-optimal image quality and multiple technical challenges involved with MRI of the lungs. Advances in MRI technology along with increased awareness about optimization of MR protocol have led to it being viewed as a feasible option for evaluation of various chest diseases in children. This short review article takes the reader to the road less travelled to explore newer horizons for applications of this rapidly evolving magnetic resonance technique in the field of thoracic diseases in children.
Keywords: children; lung; magnetic resonance imaging; pediatric